Analytical study of inflammatory cytokines and immunoglobulin expression following dust mite allergen exposure in pregnant mice - Risa Etika; Subijanto Marto Sudarmo; Suwarno Suwarno; Muhammad Pradhika Mapindra; Muhammad Pradhiki Mahindra (Paediatrica Indonesiana, 2021)
Background Allergen tolerability due to allergic immune reactions could be transferred through the placenta from maternal to fetal circulation. Hence, a further investigation regarding the tolerability following mite allergen exposures is desirable. Objective To evaluate various doses of mite allergens and cytokines associated with Th1, Th2, and Treg cells with regards to possible allergic tolerance in neonatal mice. Methods This study used an experimental design with a post-test only control group, to assess the effect of mite allergens on pregnant BALB/C mice and their newborns. In this study female BALB/C mice aged 10 weeks were mated with male mice, then pregnant BALB/C mice were exposed to allergens at 4 weeks gestation. During pregnancy, pregnant females’ blood specimens were taken to measure cytokines and immunoglobulins. Meanwhile, neonatal blood specimens were taken at 2 weeks postnatally to measure cytokines and immunoglobulins. Blood specimens from pregnant BALB/C mice and their newborns were evaluated using ELISA kits for the following cytokines: interleukin (IL)-2, interferon (IFN)-γ, interleukin (IL)-4, IL-5, IL-10, TGF-β1, as well as immunoglobulins (Ig)G-1, IgG-2a, IgG-2b, IgG3 subclass, IgM, IgA, and IgE. The case group was the group that received high and low doses of exposure, while the control group did not get exposure. Results In response to low dose mite allergen exposure, there were significant increases of IL-2, IFN-y, and IL-4, IL-5, and TGF-β1 in mothers and neonates. Pregnant mices that received high doses of allergens, however, had significant increases in IL-5 and TGF-B1; results were likewise for their offspring. Mothers and neonates, had significantly increased expression of IgG subclasses after a low dose of dust mite allergen. Following a ten-fold increase in allergen dose, the mothers showed significant increases in IgA, IgM, IgE, and IgG subclasses, whereas in neonatal mice, those immunoglobulin levels were not significantly different from control mice. Conclusion Exposure to mite allergens can trigger regulatory functions of Th1, Th2, and Tregs cells to activate their cytokines, except IL-10. The regulatory function of Tregs is dominated by TGFβ in maternal and neonatal mice, at low and high doses. Th1 cytokines express cytokines during exposure only to low-dose allergens and Th2 cells regulate IL-5 levels to both low- and high-dose allergens.